Antonius Michels en de stichting van het ‘Institute for Molecular Physics’ aan de Universiteit van Maryland - Sengers, Jan (Studium, 2014)
The Van der Waals Laboratory for Molecular Physics of the University of Amsterdam was founded before World War II by A.M.J.F. Michels (1889–1969). This paper describes how after World War II Michels was also the founder of the Institute for Molecular Physics at the University of Maryland.